ANALISIS PANJANG TUNGKAI, KELENTUKAN, DAN KESEIMBANGAN TERHADAP KECEPATAN TENDANGAN SABIT PADA ATLET PENCAK SILAT SULAWESI SELATAN - Sofyan Maulana; Ichsani Ichsani; Mutmainnah Mutmainnah (Program Studi Ilmu Keolahragaan FIK UNM, 2023)
This research is a descriptive statistical analysis which aims to analyze the leg length, flexibility and balance of the sickle kick speed of the South Sulawesi pencak silat athletes. The independent variables in this study were leg length, flexibility, and balance. While the dependent variable is the speed of the sickle kick. The population and sample in this study were 15 South Sulawesi Pencak Silat athletes. The data from the research results were obtained by giving a test to the sample with 4 tests, the first was a test of measuring the length of the legs starting from the Trohantor Major to the soles of the feet, the second was the flexibility test of the thigh muscles measured using a split, the third was a dynamic balance test measured using a balance test. dynamic, and fourth is and the speed of the crescent kick is measured by the number of kicks for 15 seconds. The data analysis technique is descriptive statistical analysis, the normality of the data is the leg length data: the Kolmogorov Smirnov value (Asymp) = (0.87> 0.05) is obtained, so it can be said that the leg length data of the South Sulawesi martial arts athletes follow a normal distribution or are normally distributed. Flexibility data: Kolmogorov Smirnov value (Asymp) = (0.77> 0.05) is obtained, so it can be said that the flexibility data of the South Sulawesi martial arts athletes follow a normal distribution or a normal distribution. Balance data: the Kolmogorov Smirnov value (Asymp) = (0.67> 0.05), it can be said that the balance data of the South Sulawesi pencak silat athletes follows a normal distribution or is normally distributed. Sickle kick speed data: Kolmogorov Smirnov value (Asymp) = (0.77> 0.05) is obtained, so it can be said that the sickle kick speed data of South Sulawesi pencak silat athletes follows a normal distribution or is normally distributed. Based on the results of data analysis, it is concluded that based on the leg length category, the better the leg length of the athlete, the better the speed of the sickle kick in the South Sulawesi Pencak Silat Athlete. Based on the flexibility category, the better the athlete's flexibility, the better the sickle kick speed for the South Sulawesi Pencak Silat Athlete. Based on the balance category, the better the athlete's balance, the better the sickle kick speed of the South Sulawesi Pencak Silat Athlete. Based on the categories of leg length, flexibility, and balance, the better the leg length, flexibility and balance of the athlete, the better the speed of the sickle kick in the South Sulawesi Pencak Silat Athlete. Keywords: linb length, flexibility, balance, sickle kick speed, Pencak Silat